Design and fabrication of an E-whisker using a PVDF ring. (23rd March 2021) - Jiang, Yani; Li, Jialing; Wang, Zhi; Qin, Yongbin; Guo, Guangming; Zheng, Zaixiang; Bian, Yixiang
Abstract: Mammalian whiskers can perceive obstacles and airflows. In this study, an electronic whisker (E-whisker) sensor was designed and fabricated by setting a PVDF ring with symmetrical electrodes on the root of a fiber beam. Vibration displacements with different waveforms were applied at the free end of the E-whisker beam to study the relationship between the vibration displacements and the output signals. The E-whisker protrusion sensing ability was investigated by driving it to sweep through the surface of a base platform. A static E-whisker beam and a swinging E-whisker were then separately placed in a wind tunnel to detect the airflow perception of the sensor. The experimental results suggested that the E-whisker could sense the frequencies and amplitudes of displacements at its free end, the height and width of a platform or the heights of other irregular protrusions; the static E-whisker could sense the magnitude or direction of an impact airflow, while the swinging E-whisker could sense the magnitude of a constant airflow. Thus, this kind of E-whisker could perceive the environment and airflow through touch sensation and could be used as a physical model to study the principles and abilities of animal whiskers to perceive obstacles and airflows.